PENGARUH DISTRIBUSI LOGISTIK TERHADAP KEPUASAN PELAYANAN PELANGGAN PADA PT. POS INDONESIA PERSERO KOTA GUNUNGSITOLI - Zebua, Roni Dermawan; Gea, Jeliswan Berkat Iman Jaya; Zebua, Serniati; Mendrofa, Martha Surya Dinata (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nommensen, 2025)
This research was conducted at PT. Pos Indonesia Gunungsitoli, researching the distribution of logistics and customer satisfaction at PT. Pos Indonesia Gunungsitoli where researchers found several phenomena or problems that occurred, namely the level of accuracy and timeliness in package delivery that were widely complained about by customers, the level of service and employee performance that were not optimal. The purpose of this study was to determine whether there was an Influence of Distribution on Customer Satisfaction at PT. Pos Indonesia Gunungsitoli City and how much influence Distribution had on Customer Satisfaction at PT. Pos Indonesia Gunungsitoli City. Respondents were 40 people. While in the data analysis test using validity test, reliability test, correlation coefficient analysis, determinant coefficient, and hypothesis test. The test results with the help of the SPSS Version 26 program, the calculation results of the Reliability Test of Variable X are 0.847 > 0.60 and Variable Y is 0.999 0.60 so that it can be stated as reliable from the Determinant Coefficient Test (R Square) showing a value of 0.55, which means that the determination value when expressed as a percentage is at a value of 55% of the distribution variable value against the customer satisfaction variable.